Efektifitas Beberapa Spesies Trichoderma spp. Terhadap Keparahan Penyakit TanamaniSeledri (Apium graveolensiL.) YangiTerinfeksi Nematoda Puru Akar (Meloidogyne spp.) - Muhammad hedir Ali; Dewi Fitriyanti; Salamiah Salamiah (JURNAL PROTEKSI TANAMAN TROPIKA, 2026)
Celery plants have many benefits, one of which is being used as an additional ingredient in cooking or as a food flavoring. Apart from being rich in benefits, celery plants also have quite promising economic value. The decline in celery production in Indonesia is also caused by root knot nematodes, Meloidogyne spp. Is one of the important pathogens in various horticultural crops and some food crops in Indonesia. Environmentally friendly pathogen control necessary done using biological agents, Trichoderma sp. is a saprophytic soil microorganism that naturally attacks pathogenic fungi and is beneficial for plants, a mechanism carried out by antagonistic agents. Trichoderma sp. against pathogens are mycoparasites and antibiotics. This study aims to determine the effectiveness of several species Trichoderma spp. in reducing nematode populations pure root (Meloidogyne spp.) on celery plants. Research This applies the Design method complete Random, which aims to obtain accurate data regarding the impact of attacks, which involves one factor, namely treatment using 500 nematode eggs as a control (P0) and using three treatments, namely (P1) = 500 nematode eggs (Meloidogyne spp.) + Trichodermaspp. from bamboo roots; (P2) = 500 nematode eggs (Meloidogyne spp.) + Trichodermaspp. from chili roots; (P3) = 500 nematode eggs (Meloidogyne spp.) + Trichodermaspp. from elephant grass roots. The results of the study showed that the treatmentTrichodermaspp. from elephant grass roots (P3) reduced disease severity by an average of 20.5% and a maximum of 61.5% (P0). The lowest root knot nematode population was 170.3 individuals (P3), while the highest population was found in the control treatment (P0), with 505.1 NPA individuals.